1995
DOI: 10.1126/science.7534442
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Effects of the Guanine Nucleotide Exchange Factor RCC1 on RNA Transport

Abstract: Transport of RNAs within nuclei and through nuclear pore complexes (NPCs) are essential, but poorly understood, steps in gene expression. In experiments with mammalian cells, RCC1, the abundant nuclear guanine nucleotide exchange factor for the guanosine triphosphatase Ran/TC4, was shown to be required for nucleocytoplasmic transport of precursors of spliceosomal small nuclear RNAs (snRNAs), intranuclear transport of U3 snRNA, and processing of ribosomal RNAs, but not for export of transfer RNAs. It is propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 39 publications
4
82
0
Order By: Relevance
“…Nonintronic snoRNAs, such as U8, which are transcribed from their own genes, are made with a monomethylguanosine cap that can be converted in the nucleus to a trimethylguanosine cap (Peculis & Steitz, 1994;Terns & Dahlberg, 1994;Cheng et al+, 1995;Terns et al+, 1995)+ Fluorescein-labeled U8 snoRNA that lacks a cap when injected is still localized in nucleoli, as can be seen in Figure 2+ As another control, U8 was synthesized with an A-cap rather than its usual G-cap (see Materials and Methods); U8 snoRNA with an A-cap cannot be trimethylated, although it is stable and can function in rRNA processing (Peculis & Steitz, 1994) and, as anticipated, localizes to nucleoli after 2 h (Fig+ 2)+ Therefore, the nucleolar localization in Xenopus oocytes does not depend on the presence or nature of the 59 cap on the injected U8 snoRNA+ U8 snoRNA synthesized with a monomethylguanosine cap was injected into oocytes for the studies described below, to emulate the in vivo situation as closely as possible+ Sequences in U8 snoRNA needed for rRNA processing are not required for nucleolar localization U8 snoRNA has been dissected by mutagenesis to define the sequences needed for rRNA processing (Peculis & Steitz, 1994;Peculis, 1997)+ Endogenous U8 snoRNA was depleted by antisense oligonucleotide injection into Xenopus oocytes, and mutated U8 snoRNA constructs were subsequently injected to assay if they could rescue the rRNA processing defect+ Those ex-periments indicated that the 59 region of U8 snoRNA was important for function in rRNA processing+ We have analyzed the mutated U8 snoRNAs used in those studies that were defective in rRNA processing to see if they can localize to nucleoli+ The failure to rescue rRNA processing could possibly reflect a secondary effect caused by inability of the mutant snoRNA to localize to nucleoli where rRNA processing occurs+ Alternatively, the sequences that were changed in the mutant snoRNA may be important only for rRNA processing, but not for nucleolar localization+ In fact, we will show here that the latter is the case for many sequences in U8+ Mutant U8 molecules examined for their ability to localize to nucleoli are listed in Figure 3+ Most of these are substitutions of sequence, but two mutants were constructed in this study that had regions of the molecule deleted (⌬82-107; ⌬St3,4)+ Table 1 summarizes previous (Peculis & Steitz, 1994) and present results of the ability of mutant U8 snoRNAs to rescue rRNA processing, and compares this to their nucleolar localization, as well as their association with the nucleolar protein, fibrillarin+ U8 snoRNA mutants that had substitutions of sequences found in loops and that lost function in rRNA processing were analyzed for their nucleolar localization+ As a positive control, we analyzed U8 loop mutant Lp4M, which is known to retain its function in rRNA processing (Peculis & Steitz, 1994) and therefore must presumably be localized in nucleoli+ Indeed, the Lp4M mutant localized to nucleoli (Fig+ 4)+ Similarly, loop mutants Lp1M and Lp2M localized to nucleoli (Fig+ 4), even though they cannot function in rRNA processing …”
Section: Localization Of Xenopus U8 Wild-type Snorna To Nucleolimentioning
confidence: 99%
“…Nonintronic snoRNAs, such as U8, which are transcribed from their own genes, are made with a monomethylguanosine cap that can be converted in the nucleus to a trimethylguanosine cap (Peculis & Steitz, 1994;Terns & Dahlberg, 1994;Cheng et al+, 1995;Terns et al+, 1995)+ Fluorescein-labeled U8 snoRNA that lacks a cap when injected is still localized in nucleoli, as can be seen in Figure 2+ As another control, U8 was synthesized with an A-cap rather than its usual G-cap (see Materials and Methods); U8 snoRNA with an A-cap cannot be trimethylated, although it is stable and can function in rRNA processing (Peculis & Steitz, 1994) and, as anticipated, localizes to nucleoli after 2 h (Fig+ 2)+ Therefore, the nucleolar localization in Xenopus oocytes does not depend on the presence or nature of the 59 cap on the injected U8 snoRNA+ U8 snoRNA synthesized with a monomethylguanosine cap was injected into oocytes for the studies described below, to emulate the in vivo situation as closely as possible+ Sequences in U8 snoRNA needed for rRNA processing are not required for nucleolar localization U8 snoRNA has been dissected by mutagenesis to define the sequences needed for rRNA processing (Peculis & Steitz, 1994;Peculis, 1997)+ Endogenous U8 snoRNA was depleted by antisense oligonucleotide injection into Xenopus oocytes, and mutated U8 snoRNA constructs were subsequently injected to assay if they could rescue the rRNA processing defect+ Those ex-periments indicated that the 59 region of U8 snoRNA was important for function in rRNA processing+ We have analyzed the mutated U8 snoRNAs used in those studies that were defective in rRNA processing to see if they can localize to nucleoli+ The failure to rescue rRNA processing could possibly reflect a secondary effect caused by inability of the mutant snoRNA to localize to nucleoli where rRNA processing occurs+ Alternatively, the sequences that were changed in the mutant snoRNA may be important only for rRNA processing, but not for nucleolar localization+ In fact, we will show here that the latter is the case for many sequences in U8+ Mutant U8 molecules examined for their ability to localize to nucleoli are listed in Figure 3+ Most of these are substitutions of sequence, but two mutants were constructed in this study that had regions of the molecule deleted (⌬82-107; ⌬St3,4)+ Table 1 summarizes previous (Peculis & Steitz, 1994) and present results of the ability of mutant U8 snoRNAs to rescue rRNA processing, and compares this to their nucleolar localization, as well as their association with the nucleolar protein, fibrillarin+ U8 snoRNA mutants that had substitutions of sequences found in loops and that lost function in rRNA processing were analyzed for their nucleolar localization+ As a positive control, we analyzed U8 loop mutant Lp4M, which is known to retain its function in rRNA processing (Peculis & Steitz, 1994) and therefore must presumably be localized in nucleoli+ Indeed, the Lp4M mutant localized to nucleoli (Fig+ 4)+ Similarly, loop mutants Lp1M and Lp2M localized to nucleoli (Fig+ 4), even though they cannot function in rRNA processing …”
Section: Localization Of Xenopus U8 Wild-type Snorna To Nucleolimentioning
confidence: 99%
“…As shown in Fig. 11, E and F, losartan, but An amino acid sequence analysis revealed that GLP protein contains a motif similar to that of the RCC1 gene, which is a GEF for small G-protein Ran (52)(53)(54)(55)(56)(57). In addition to a seventandem-repeat motif, GLP has an extra carboxyl-terminal tail that the RCC1 gene does not possess (See Fig.…”
Section: Hypertrophic Effects Of the Glp Gene In Irptcs-irptcsmentioning
confidence: 99%
“…This protein was subsequently shown to catalyze the guanine nucleotide exchange on Ran, a nuclear GTPbinding protein and a member of the Ras superfamily of small GTPases (Bischo and Ponstingl, 1991). More recently, RCC1 and Ran have been implicated in nucleocytoplasmic transport (Cheng et al, 1995;Moore and Blobel, 1994;Ren et al, 1995;Schlenstedt et al, 1995).…”
mentioning
confidence: 99%